Choanal atresia: the 13 years’ experience of our department - Fernandes Lopes, Patrícia (2024)
Objective: To audit our experience with Choanal Atresia (CA). Study design: Observational retrospective study. Material/Methods: Clinical data of all CA patients followed from 2003 to 2020 at Hospital Central do Funchal were analysed. Results: Eleven patients were included and 63,64% were females. They were divided into two groups: Unilateral (63,64%) and bilateral atresia (36,36%). In both groups, mixed type atresia was the most common. Regarding unilateral group, endoscopic repair was performed in 85,71% of cases (71,4% with stents) at a median age of 15 years old. Median number of surgeries was 1,29. Bilateral group had more congenital malformations (50%) and had more reinterventions. All patients underwent an endoscopic approach at a median age of 8 days old. Conclusions: Associated malformations, younger age at first surgery and higher number of surgeries were more associated to bilateral CA.